Das Tier in dir - Kreaturen in (und außerhalb) der mumok Sammlung Museum moderner Kunst Stiftung Ludwig Wien - Ammer, Manuela 1977-; Müller, Ulrike; Amir, Fahim; Halberstam, Jack 1961-; Hayward, Eva; Hedva, Johanna; Kapil, Bhanu 1968-; Murphy, Joni; Sanlan, Kathryn; Seshadri-Crooks, Kalpana 1960-; Stakemeier, Kerstin 1975-; Timofeeva, Oxana 1978-; et al. (mumok, 2022)
Visual art and its fascination with animals (in the form of pets, zoo animals, farm animals, stuffed animals, along with projections of wildness) prepare the ground to reflect on the nature of sex, hunger, and affection, as well as on family and gender relations, socialization and domestication, and, not least, on the enduring impact of colonial history
Impressum: Dieses Buch erscheint anlässlich der Ausstellung "Das Tier in dir. Kreaturen in (und außerhalb) der mumok Sammlung", 22. September 2022 bis 26. Februar 2023, mumok - Museum moderner Kunst Stiftung Ludwig Wien
Keywords: Museum Moderner Kunst Stiftung Ludwig; Geschichte 1924-2020; Geschichte 1960-2022; Sammlung; Tierdarstellung; Tiere; Kunst; Mensch; Zeitgenössische Kunst; Ausstellung; Museum moderner Kunst Stiftung Ludwig Wien; Ausstellungskatalog -- Museum Moderner Kunst Stiftung Ludwig -- 22.09.2022-26.02.2023 -- Wien